Performance Analysis of a Spectral-Efficient High-Speed Hybrid PDM-MDM Enabled Integrated MMF-FSO Transmission - Somia A. Abd El-Mottaleb; Mehtab Singh; Hassan Yousif Ahmed; Median Zeghid; Kottakkaran Sooppy Nisar (IEEE Photonics Journal)
This article proposes a novel 2 × 4 × 10 Gbps hybrid multi-mode-fiber (MMF) free-space optics-communication (FSOC) system based on integrating two multiplexing techniques; polarization-division-multiplexing (PDM) and mode-division-multiplexing (MDM). Two polarization states are used, each of these states carries four different Hermite Gaussian (HG) modes while each HG modes carries 10 Gbps data. Performance analysis is investigated by considering fixed length of MMF cable and varying FSOC range in absence and presence of different atmospheric turbulences (weak turbulence (WT) and strong turbulence (ST)). Additionally, it is evaluated also by taking a fixed range for FSO link and considering ideal scintillation with different MMF lengths. Moreover, it is investigated under rainy weather of Alexandria city in Egypt, Pune city in India, and Jeddah city in the Kingdom-of-Saudi-Arabia (KSA). The link distance, beam-angle, eye-diagrams, and bit-error-rate are the parameters that used for evaluating the system's performance. The results after simulating model using optisystem reveal 80 Gbps overall transmission capacity at 1500 m (100 m MMF + 1400 m FSO link) in the presence of ST, while for fixed FSO link (100 m), the achievable transmission is 350 m. The overall ranges of 1300 m, 1200 m, and 1600 m are achieved for Alexandria, Pune, and Jeddah.